(untitled) (Academia Journal of Medicine, 2026)
Background: Chest pain represents one of the most common and challenging presentations in emergency medicine, requiring rapid differentiation between life-threatening cardiac conditions and benign etiologies. The HEART score was developed to risk stratify patients with chest pain for major adverse cardiac events (MACE), yet validation across diverse populations and healthcare settings remains essential for confident clinical implementation. Methods: A prospective observational cohort study was conducted at our tertiary care hospital over 20 months, enrolling 892 adult patients presenting with chest pain suggestive of possible acute coronary syndrome. HEART scores were calculated at presentation, and patients were followed for 6 weeks. The primary outcome was occurrence of MACE, defined as acute myocardial infarction, percutaneous coronary intervention, coronary artery bypass grafting, or all-cause mortality. Results: The mean age was 54.8 ± 14.2 years, with 58.4% male patients. The mean HEART score was 4.2 ± 1.8. MACE occurred in 142 patients (15.9%). The area under the ROC curve for MACE prediction was 0.867 (95% CI: 0.838–0.896). Low-risk patients (HEART score 0-3) experienced MACE in 2.1% of cases (8/386), intermediate-risk (score 4-6) in 18.4% (68/370), and high-risk (score 7-10) in 48.5% (66/136). A HEART score ≤3 demonstrated 94.4% sensitivity and 65.7% specificity with negative predictive value of 97.9%. Conclusion: The HEART score demonstrates excellent discriminatory ability for predicting MACE in patients with undifferentiated chest pain, effectively identifying low-risk patients suitable for early discharge and outpatient management.